Nitrogen spraying affects seed Bt toxin concentration and yield in Bt cotton - Xiang ZHANG; Ming-yuan ZHOU; Ya-bing LI; Zhen-yu LIU; Yuan CHEN; De-hua CHEN (Journal of Integrative Agriculture, 2021)
Cotton bolls exhibit the lowest insecticidal efficacy among all organs of Bt cotton, which would ultimately affect the yield formation. The objective of this study was to investigate the effects of different urea concentrations on the seed Bt protein contents, seed cotton yield and the corresponding protein metabolism mechanism. The experiments were conducted during 2017–2018 cotton growing seasons. Two cultivars, Sikang 3 (hybrid, SK3) and Sikang 1 (conventional, SK1), were treated with six urea concentrations and their seed Bt protein contents were compared during boll formation period. The urea spray concentration had a significant effect on the seed Bt toxin content and seed cotton yield. Spraying of either 5 or 6% urea led to higher insecticidal protein contents and higher seed cotton yield for both cultivars. Moreover, the highest amino acid and soluble protein contents, as well as GPT and GOT activities, and lower protease and peptidase activities were observed at the 5 to 6% urea levels. Significant positive correlations between the seed Bt toxin and amino acid contents, and between the seed Bt toxin content and GPT activities were detected. The lower boll worm number and hazard boll rate were also observed with the 5 to 6% urea treatments, which may be the reason why nitrogen spraying increased the seed cotton yield. Therefore, our results suggested that the seed Bt toxin content and insect resistance were impacted markedly by external nitrogen application, and 5 to 6% urea had the greatest effect on insect resistance.